Teaching and Learning in Kenya: Examining the Shifts in Cultural Learning of Experienced Educators - Hockett, Eloise (Journal of research on christian education, 2018)
This qualitative case study examined the cultural learning insights of four educators during and after an immersion experience in Kenya. During this experience the participants delivered professional development sessions to teachers in two rural Kenyan schools, and stayed with Kenyan families. Mezirow's transformational learning theory, self-reflection, and cultural humility were utilized as a framework to examine the educators' learning experiences. Data were collected through pre-trip planning sessions, journals, debriefing sessions, field notes, and a 6-month follow-up interview. Results of the data produced five main themes: (1) general observations; (2) recognizing biases and assumptions; (3) cultural insights; (4) cultural humility; and (5) spiritual insights. Even though these participants had prior interactions with different cultures, this trip expanded their experiences and provided them with further understanding of how to interact with different cultures abroad, and within their professional contexts. While cultural aspects tend to be emphasized in undergraduate programs, these experienced educators benefitted from this cultural immersion experience, which could be used to make a case for continuing the same emphasis in graduate programs.